Assertive Illocutionary Acts in Kim Nam Joon’s (RM) Speech at the APEC CEO Summit Korea 2025 - Giacinta Azzahra; Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2026)
This study examines assertive illocutionary acts in RM’s speech as the leader of BTS at the Asia-Pacific Economic Cooperation (APEC) CEO Summit, drawing on Searle’s (1969) speech act theory. Language in international forums serves not merely to convey information but also to establish credibility, represent particular perspectives, and influence global audiences. RM’s participation in the APEC CEO Summit reflects the growing role of celebrity figures in international discussions concerning culture, economics, and global cooperation. Previous studies on speech acts have primarily focused on political speeches, classroom interactions, films, and social media communication. However, relatively few studies have investigated assertive illocutionary acts in celebrity diplomacy speeches delivered within international political-economic forums. Research related to BTS or RM has likewise largely centered on fandom, identity, and popular culture, while the linguistic strategies used to construct authority and represent cultural diplomacy remain underexplored. Therefore, this study specifically focuses on assertive illocutionary acts because they reveal how speakers present facts, articulate beliefs, and communicate viewpoints in formal public discourse. Using a descriptive qualitative approach, data were obtained from RM’s speech uploaded on the official KBS News YouTube channel through observation, listening, and transcription. The findings reveal 31 utterances of assertive illocutionary acts used to present facts, articulate perspectives, and frame cultural and economic issues, particularly K-pop as a creative industry contributing to global economic development. The study highlights the strategic use of assertive illocutionary acts in celebrity diplomacy and the representation of youth voices within international forums